Comparison of methods for identification of microbial communities in book collections: Culture-dependent (sequencing and MALDI-TOF MS) and culture-independent (Illumina MiSeq). (July 2018) - Kraková, Lucia; Šoltys, Katarína; Otlewska, Anna; Pietrzak, Katarzyna; Purkrtová, Sabina; Savická, Dana; Puškárová, Andrea; Bučková, Mária; Szemes, Tomáš; Budiš, Jaroslav; Demnerová, Kateřina; Gutarowska, Beata; et al.
Abstract: Different identification strategies employing new methodologies, namely, culture-dependent (using matrix-assisted laser desorption/ionization – time-of-flight mass spectrometry, MALDI-TOF MS) and culture-independent (using high-throughput sequencing on Illumina MiSeq platform) approaches, were applied for the first time to analysis of the deteriorating microflora of book samples. We compared two different identification techniques coupled to microbial cultivation: DNA sequencing and MALDI-TOF MS. The two identification systems produced almost the same results. DNA sequencing was able to better identify all the recovered isolates, while MALDI-TOF MS failed to properly recognize Streptomyces ambofaciens and Lysinibacillus fusiformis, the latter method permitting identification at least at genus level. In addition, the isolates Myxotrichum deflexum and Oidiodendron cerealis were not identified by the MALDI-TOF MS approach. This incongruence was caused by the absence of different kinds of microorganisms in the MALDI BioTyper reference database. The Illumina high-throughput sequencing coupled to non-invasive sampling allowed the identification of a complex bacterial and fungal community. The study presents the satisfactory performance of two novel alternative identification methods (MALDI-TOF MS and Illumina MiSeq) for the investigation of microflora colonizing archival items. Highlights: Microbial deteriogens of book surfaces were identified. Novel identification techniques MALDI-TOF MS and Illumina high-throughput sequencing were applied. Culture-dependent- based approach: MALDI-TOF MS and DNA sequencing were compared. The identification by MALDI-TOF MS and DNA sequencing produced similar results. High-throughput sequencing allowed a deep identification of colonizing microflora.